Penerapan Metode Fast Fourier Transform Dalam Perbaikan Kualitas Tampak Wajah Maling Sepeda Motor - Lenny Suryani Lumban Gaol (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
Image improvement is an image processing process that is indispensable to improve poor image quality. Image quality improvement can be used to make it easier to recognize the face of a thief caught by CCTV. One of the methods used to improve image quality is by using the Fast Fourier Transform method. The results of facial image quality improvement using the Fast Fourier Transform method are used to improve the quality of facial images so that the image captured by CCTV can be seen clearly. Thus the campus can more easily recognize the thief's face. To make it easier to solve this problem, image enhancement is carried out using the Fast Fourier Transform method. The process of improving the quality of the face image also uses the VB.Net 2008 program, the inputted data is in the form of a thief's face then processed and produces a better image quality output of the thief's face.